The Role of Organizational Learning in Mediating the Relationship between Business Model Design and Innovation Performance - Jia Zhang; Hui Xu; Xiangxia Xiao (Discrete Dynamics in Nature and Society)
Innovation in the business model (BM) may be irreversible and therefore entails more significant risk and ambiguity compared to product, service, or process innovation. This paper focused on exploring the role of organizational learning in mediating the relationship between business model design and innovation performance using hierarchical hybridized linear regression analysis (HHLRA). Furthermore, this paper shows that organizational learning is based on variables that mediate the relationship between training and performance and improve performance through its positive effect on organizational learning. Furthermore, the study examines the multi-dimensional and contingent progressive impact on the corporate performance of organizational training through innovative conjunctive roles. However, this study determines that both organizational learning capabilities (OLC) and organization innovativeness (OI) have a positive effect on organizational performance (OP). Besides, organizational innovativeness mediates the relationship between OLC and OI. Finally, the findings suggest that managers should improve organizational learning capabilities and improve innovation performance to enhance positive entrepreneurial orientation performance connections.